Differential analysis of competitive anxiety and psychological skills predictive of the result in a softball championship - Ríos Garit, Jesús (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2025)
The aim of this research is to determine the relevant psychological variables for obtaining highly competitive results in a national women's softball championship. A cross-sectional and correlational study was carried out in which 90 high-performance athletes distributed in 6 teams from different provinces of Cuba participated. The female softball players had an average chronological age of 22.91 years and 10.83 years of sports experience. The Competitive Anxiety Inventory and the Psychological Inventory of Sports Performance were applied to evaluate anxiety in competition and the psychological skills associated with sports performance in the first week of the competition. The data were analyzed using descriptive, inferential, and correlational statistics. In general, the athletes presented high levels of competitive anxiety, being higher in the younger and less experienced ones. A higher level of competition anxiety was related to lower negative coping and attention control. The athletes from the teams that achieved better results had greater self-confidence, control of negative coping, attention, and motivational level. These variables positively predict the greatest competitive result, which shows the importance of psychological preparation for competition to achieve success.